A fast algorithm for building the octree for a three-dimensional object from its multiple images - Noborio, H.; Fukuda, S.; Arimoto, S. (Pattern Recognition, 9th International Conference on, 1988: Proceedings, 2003)
A fast algorithm is presented to measure obstacle shape in the workspace and to register the shape to the octree that is suitable for path and motion planning of the robot. The octree is constructed hierarchically by a set of cubic regions in the workspace, and its data structure is suitable for detecting interference between a moving robot and its obstacles and searching for a free region in the robot path planning.< >